Perovskite-structured CaTiO3 coupled with g-C3N4 as a heterojunction photocatalyst for organic pollutant degradation - Kumar, Ashish; Schuerings, Christian; Kumar, Suneel; Kumar, Ajay; Krishnan, Venkata (Beilstein Journal of Nanotechnology, 2018)
A novel graphitic carbon nitride (g-C3N4)–CaTiO3 (CTCN) organic–inorganic heterojunction photocatalyst was synthesized by a facile mixing method, resulting in the deposition of CaTiO3 (CT) nanoflakes onto the surface of g-C3N4 nanosheets. The photocatalytic activity of the as-synthesized heterojunction (along with the controls) was evaluated by studying the degradation of an aqueous solution of rhodamine B (RhB) under UV, visible and natural sunlight irradiation. The CTCN heterojunction with 1:1 ratio of g-C3N4/CT showed the highest photocatalytic activity under sunlight irradiation and was also demonstrated to be effective for the degradation of a colorless, non-photosensitizing pollutant, bisphenol A (BPA). The superior photocatalytic performance of the CTCN heterojunction could be attributed to the appropriate band positions, close interfacial contact between the constituents and extended light absorption (both UV and visible region), all of which greatly facilitate the transfer of photogenerated charges across the heterojunction and inhibit their fast recombination. In addition, the two-dimensional (2D) morphology of g-C3N4nanosheets and CT nanoflakes provides enough reaction sites due to their larger surface area and enhances the overall photocatalytic activity. Furthermore, the active species trapping experiments validate the major role played by superoxide radicals (O2−•) in the degradation of pollutants. Based on scavenger studies and theoretically calculated band positions, a plausible mechanism for the photocatalytic degradation of pollutants has been proposed and discussed.
Keywords: CaTiO3; graphitic carbon nitride (g-C3N4); heterojunction photocatalyst; pollutant degradation

(untitled) - Cao, S.; Low, J.; Yu, J.; Jaroniec, M. (Adv. Mater., 2015)

(untitled) - Ong, W.-J.; Tan, L.-L.; Ng, Y. H.; Yong, S.-T.; Chai, S.-P. (Chem. Rev., 2016)

(untitled) - Zhang, G.; Li, G.; Lan, Z.-A.; Lin, L.; Savateev, A.; Heil, T.; Zafeiratos, S.; Wang, X.; Antonietti, M. (Angew. Chem., Int. Ed., 2017)

(untitled) - Kumar, S.; Kumar, A.; Bahuguna, A.; Sharma, V.; Krishnan, V. (Beilstein J. Nanotechnol., 2017)

(untitled) - Zhao, Z.; Sun, Y.; Dong, F. (Nanoscale, 2015)

(untitled) - Zhang, G.; Lan, Z.-A.; Lin, L.; Lin, S.; Wang, X. (Chem. Sci., 2016)

(untitled) - Xu, Q.; Cheng, B.; Yu, J.; Liu, G. (Carbon, 2017)

(untitled) - Sun, Z.; Kim, J. H.; Zhao, Y.; Bijarbooneh, F.; Malgras, V.; Lee, Y.; Kang, Y.-M.; Dou, S. X. (J. Am. Chem. Soc., 2011)

(untitled) - Cao, S.; Yu, J. (J. Phys. Chem. Lett., 2014)

(untitled) - Jiang, D.; Wang, T.; Xu, Q.; Li, D.; Meng, S.; Chen, M. (Appl. Catal., B: Environ., 2017)

(untitled) - Ong, W.-J. (Front. Mater., 2017)

(untitled) - Hou, Y.; Laursen, A. B.; Zhang, J.; Zhang, G.; Zhu, Y.; Wang, X.; Dahl, S.; Chorkendorff, I. (Angew. Chem., Int. Ed., 2013)

(untitled) - Cheng, H.; Hou, J.; Takeda, O.; Guo, X.-M.; Zhu, H. (J. Mater. Chem. A, 2015)

(untitled) - Zhang, Z.; Huang, J.; Zhang, M.; Yuan, Q.; Dong, B. (Appl. Catal., B: Environ., 2015)

(untitled) - Xiang, Q.; Yu, J. (J. Phys. Chem. Lett., 2013)

(untitled) - Niu, P.; Zhang, L.; Liu, G.; Cheng, H.-M. (Adv. Funct. Mater., 2012)

(untitled) - Zhang, Y.; Liu, J.; Wu, G.; Chen, W. (Nanoscale, 2012)

(untitled) - Zhang, G.; Lan, Z.-A.; Wang, X. (Chem. Sci., 2017)

(untitled) - Cheng, F.; Yin, H.; Xiang, Q. (Appl. Surf. Sci., 2017)

(untitled) - Barman, S.; Sadhukhan, M. (J. Mater. Chem., 2012)

(untitled) - Zheng, Y.; Liu, J.; Liang, J.; Jaroniec, M.; Qiao, S. Z. (Energy Environ. Sci., 2012)

(untitled) - Wang, H.; Yuan, X.; Wu, Y.; Zeng, G.; Chen, X.; Leng, L.; Li, H. (Appl. Catal., B: Environ., 2015)

(untitled) - Tong, Z.; Yang, D.; Shi, J.; Nan, Y.; Sun, Y.; Jiang, Z. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Guo, S.; Deng, Z.; Li, M.; Jiang, B.; Tian, C.; Pan, Q.; Fu, H. (Angew. Chem., Int. Ed., 2016)

(untitled) - Shi, L.; Liang, L.; Wang, F.; Liu, M.; Zhong, S.; Sun, J. (Catal. Commun., 2015)

(untitled) - Lin, Q.; Li, L.; Liang, S.; Liu, M.; Bi, J.; Wu, L. (Appl. Catal., B: Environ., 2015)

(untitled) - Li, Q.; Zhang, N.; Yang, Y.; Wang, G.; Ng, D. H. L. (Langmuir, 2014)

(untitled) - Jiang, Z.; Jiang, D.; Yan, Z.; Liu, D.; Qian, K.; Xie, J. (Appl. Catal., B: Environ., 2015)

(untitled) - Savateev, A.; Pronkin, S.; Epping, J. D.; Willinger, M. G.; Wolff, C.; Neher, D.; Antonietti, M.; Dontsova, D. (ChemCatChem, 2017)

(untitled) - Xian, T.; Yang, H.; Di, L. J.; Dai, J. F. (J. Alloys Compd., 2015)

(untitled) - Jo, W.-K.; Natarajan, T. S. (Chem. Eng. J., 2015)

(untitled) - Reddy, J. R.; Kurra, S.; Guje, R.; Palla, S.; Veldurthi, N. K.; Ravi, G.; Vithal, M. (Ceram. Int., 2015)

(untitled) - Subramanian, V.; Roeder, R. K.; Wolf, E. E. (Ind. Eng. Chem. Res., 2006)

(untitled) - Leong, K. H.; Tan, Z. Z.; Sim, L. C.; Saravanan, P.; Bahnemann, D.; Jang, M. (ChemistrySelect, 2017)

(untitled) - Zhang, H.; Chen, G.; Li, Y.; Teng, Y. (Int. J. Hydrogen Energy, 2010)

(untitled) - Kumar, A.; Kumar, S.; Bahuguna, A.; Kumar, A.; Sharma, V.; Krishnan, V. (Mater. Chem. Front., 2017)

(untitled) - Wang, W.; Tadé, M. O.; Shao, Z. (Chem. Soc. Rev., 2015)

(untitled) - Xian, T.; Yang, H.; Huo, Y. S. (Phys. Scr., 2014)

(untitled) - Kumar, S.; Reddy, N. L.; Kumar, A.; Shankar, M. V.; Krishnan, V. (Int. J. Hydrogen Energy, 2017)

(untitled) - Cheng, Y.-Y.; Tsai, T.-H. (J. Agric. Food Chem., 2017)

(untitled) - Kumar, S.; Sharma, V.; Bhattacharyya, K.; Krishnan, V. (New J. Chem., 2016)

(untitled) - Sharma, V.; Harith, G.; Kumar, S.; Sharma, R.; Reddy, K. L.; Bahuguna, A.; Krishnan, V. (Mater. Technol., 2017)

(untitled) - Wang, Y.; Niu, C.-G.; Wang, L.; Wang, Y.; Zhang, X.-G.; Zeng, G.-M. (RSC Adv., 2016)

(untitled) - Liu, H.; Jin, Z.; Xu, Z.; Zhang, Z.; Ao, D. (RSC Adv., 2015)

(untitled) - Di, J.; Xia, J.; Yin, S.; Xu, H.; Xu, L.; Xu, Y.; He, M.; Li, H. (J. Mater. Chem. A, 2014)

(untitled) - Fu, M.; Liao, J.; Dong, F.; Li, H.; Liu, H. (J. Nanomater., 2014)

(untitled) - Lee, S.-W.; Lozano-Sánchez, L. M.; Rodríguez-González, V. (J. Hazard. Mater., 2013)

(untitled) - Lewis, C. S.; Liu, H.; Han, J.; Wang, L.; Yue, S.; Brennan, N. A.; Wong, S. S. (Nanoscale, 2016)

(untitled) - Tian, Y.; Chang, B.; Lu, J.; Fu, J.; Xi, F.; Dong, X. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Liu, C.; Zhang, Y.; Dong, F.; Reshak, A. H.; Ye, L.; Pinna, N.; Zeng, C.; Zhang, T.; Huang, H. (Appl. Catal., B: Environ., 2017)

(untitled) - Bhirud, A.; Sathaye, S.; Waichal, R.; Park, C.-J.; Kale, B. (J. Mater. Chem. A, 2015)

(untitled) - Liu, C.; Huang, H.; Du, X.; Zhang, T.; Tian, N.; Guo, Y.; Zhang, Y. (J. Phys. Chem. C, 2015)

(untitled) - Zhang, X.-S.; Hu, J.-Y.; Jiang, H. (Chem. Eng. J., 2014)

(untitled) - Kumar, S.; Sharma, V.; Bhattacharyya, K.; Krishnan, V. (Mater. Chem. Front., 2017)

(untitled) - Sharma, V.; Kumar, S.; Krishnan, V. (ChemistrySelect, 2016)

(untitled) - Uddin, M. J.; Islam, M. A.; Haque, S. A.; Hasan, S.; Amin, M. S. A.; Rahman, M. M. (Int. Nano Lett., 2012)

(untitled) - Gu, Z.; Thomas, A. C.; Xu, Z. P.; Campbell, J. H.; Lu, G. Q. (Chem. Mater., 2008)

(untitled) - Ohko, Y.; Ando, I.; Niwa, C.; Tatsuma, T.; Yamamura, T.; Nakashima, T.; Kubota, Y.; Fujishima, A. (Environ. Sci. Technol., 2001)

(untitled) - Jiang, F.; Yan, T.; Chen, H.; Sun, A.; Xu, C.; Wang, X. (Appl. Surf. Sci., 2014)

(untitled) - Zang, Y.; Li, L.; Xu, Y.; Zuo, Y.; Li, G. (J. Mater. Chem. A, 2014)

(untitled) - Min, Y.; He, G.; Xu, Q.; Chen, Y. (J. Mater. Chem. A, 2014)

(untitled) - Wang, D.; Xu, Y.; Sun, F.; Zhang, Q.; Wang, P.; Wang, X. (Appl. Surf. Sci., 2016)